Decoupling impact and public utility conservation investment. (July 2019) - Michelfelder, Richard A.; Ahern, Pauline; D'Ascendis, Dylan
Abstract: Public utilities and regulators are implementing various forms of regulatory mechanisms that decouple revenues from commodity sales to remove a disincentive or create an incentive for utilities to invest in and encourage consumers to conserve electricity, natural gas and water. A major question is whether such regulatory mechanisms affect investor-perceived risk, the cost of common equity and the utility rates of such commodities. This is an important question as regulators in the US are and have been considering the impact of decoupling on investment risk and therefore the cost of common equity in rate proceedings. This matter is also important for regulators globally as they consider decoupling as a policy initiative in setting rates and rate of return. Currently, decoupling is primarily a US ratemaking policy for energy and water utilities as are price caps in Europe. Empirical testing, based on the available data in the US, consistently demonstrates that decoupling has no statistically measurable impact on risk and the cost of common equity. Therefore, at this juncture, policy is moving ahead, at least in the US, without empirical evidence on whether it does have impact on risk and return. Highlights: Revenue – sales decoupling is seen by utility management and regulators as reducing risk. Decoupling may increase or decrease investors' perceived risk of public utilities, but not actual risk. Empirical results show that decoupling has no impact on the cost of common equity capital and risk. Policy recommendation for regulation is to not adjust the allowed rate of return due to decoupling.